Pengaruh Pembelajaran Diferensiasi Terhadap Peningkatan Hasil Belajar Passing Sepak Bola Siswa Kelas Xii Sman 1 Teluk Jambe Barat - Hanif Zufar Rabbani; Dhika Bayu Mahardhika; Tedi Purbangkara (Jurnal Porkes, 2026)
The main problem of this study is the low passing skills of students at SMAN 1 Telukjambe Barat due to conventional learning that is uniform in nature. The study aims to examine the effect of differentiated learning on improving passing skills. The method used is a quasi-experiment with a Nonequivalent Control Group Design involving 70 twelfth-grade students divided into an experimental group (differentiated learning) and a control group (conventional learning). Data were collected through a passing test adapted from Nurcahyo (2014), which had been tested for validity (Aiken's V=0.87) and reliability (ICC=0.89). Statistical analysis showed a significant difference in post-test scores between the experimental and control groups (t=3.082; p=0.003). The effectiveness of learning was measured using N-Gain, which showed a moderate category (34.93%) in the experimental group and a low category (9.62%) in the control group. The discussion revealed that this success was supported by the fulfillment of basic psychological needs (competence, autonomy, connectedness) and the application of pedagogical scaffolding in accordance with Vygotsky and Deci & Ryan's theories. The conclusion of the study proves that differentiated learning effectively improves soccer passing skills significantly. The practical implication is that physical education teachers are recommended to apply a differentiated approach through initial diagnosis, tiered activities, and specific feedback to accommodate student diversity.